Estado coercitivo y reacción subalterna en Manabí durante la expansión mundial capitalista, siglo XIX (Estudios) - Hidrovo Quiñónez, Tatiana María del Carmen (2025)
This article examines the relationship between warfare and demands for freedom by subordinates caused by the penetration of the oligarchic republican state and global capitalism in its expansionary phase (19th Century) in the province of Manabí (Ecuador). It seeks to delve deeper into the studies of the multiple long-lasting armed uprisings that persisted in various regions in relation to the phases of global capitalist expansion.